Sikap guru terhadap disiplin dalam pengajaran dan pembelajaran, tahap pengetahuan, tahap pengetahuan kandungan pedagogi dan hubungannya dengan tahap kemahiran guru - Siti Maryam, Latuwo (2010)
This study is to identify the teachers' attitudes towards discipline in the area teaching and learning, teachers' knowledge, teachers' pedagogical knowledge and its relationship to teachers' skills. An adapted survey from Thock's study (2003), Ishak (2004) and additional item of pedagogical knowledge developed by Jemaah Nazir in 'Pemantauan dan Bimbingan Pelaksanaan Pengajaran dan Pembelajaran Sains dan Matematik dalam Bahasa Inggeris' are used as the case instruments. The study's sample are 110 teachers who are randomly picked from three primary schools in Sandakan, Sabah. The accumulated data is analysed using SPSS version 12.0 software. The statistics used in this study is descriptive statistics that involves frequency, percentages, mean, standard deviation and rank order while inferential statistics involves t-test at significant p < .05 and Pearson Correlation. The findings show that gender does not influence teachers' attitude towards discipline in teaching and learning, their pedagogical knowledge and also skills. However, there is a different when it comes to teachers' knowledge based of on gender. In addition, it also shows that there is a significant relationship between i) teachers' attitude towards discipline in teaching and learning and their skills; ii) teachers' knowledge and their skills; and, iii) teachers' pedagogical knowledge and their skill